Tax Evasion: Concept, Causes and Forms at the Macro and Microeconomic Level - Nițu Maria (Ovidius University Annals: Economic Sciences Series, 2018)
Tax evasion is an important topic of national and international taxation. The research carriedout by this paper highlights the definition of the notion of tax evasion by established authors, theobjectives of the paper being to point out that this negative phenomenon of tax evasion hasundesirable macroeconomic effects for the economy, in the sense that tax evasion does not allowthe state to collect the budgetary resources required. Another objective of the paper was toreconsider the categories and forms of tax evasion by pointing out that the state is responsible forit, mainly due to the legislative vacuum of the 1990s - the first law on combating tax evasion wasadopted in 1994, but this was also due to taxpayers' behavior that was permanently opposed tostate measures to amplify national taxation by introducing new taxes and duties, by increasingtheir amount or by applying unclear taxes and duties.